The Influence Of Legal Philosophy On The Dynamics Of Modern Law Formation (Case Study Of Students Of The Faculty Of Sharia And Law) - Nandani Zahara Mahfuzah; Faisar Ananda Arfa; Nurasiah, Nurasiah (Jurnal Multidisiplin Sahombu, 2025)
The purpose of this study was to determine the influence of legal philosophy on the dynamics of modern law formation, with a focus on students of the Faculty of Sharia and Law. Philosophy of law as a discipline that studies the foundations and principles of law has an important role in shaping students' understanding and views of the law. This research applies quantitative methods, by distributing questionnaires to 100 students of the Faculty of Sharia and Law, State Islamic University of North Sumatra. The results of this study indicate that the regression coefficient value is 1. 984 with a t value of 3.293 and a significance of 0.001 from the F test, namely the value of F count ˃ F table, namely 11.435 ˃ 3.09 and the Sig value ˂ 0.05, then 0.001˂ 0.05. So that the conclusion is obtained in the F test that Ha is Ha. So it is concluded in the F test that Ha3 is accepted and Ho3 is rejected. the regression coefficient of the legal philosophy variable (X) is 0.518, so that if the learning style variable decreases by 1%, if the variable is considered constant, the Dynamics of Modern Law Formation will increase by 0.521%. This study shows that the Adjusted R Square value is 0.770 or 77%. This means that the influence between the independent variables, namely the philosophy of law, is 77% while 23% is influenced by other factors that are not included in the regression model.